Implementación de un módulo didáctico para la asignatura de sistemas de control oleoneumático en la UTC Extensión La Maná. - Tinoco García, Yosselin Thalia (2024)
The implementation of a didactic module for the subject of Oleopneumatic Control Systems at UTC La Maná Extension has the purpose of solving one of the needs of the students of the Electromechanics career because in the subject of Oleopneumatic Control Systems, all the students of this subject cannot practice at the same time, since the laboratory has a simple and not automated didactic module and therefore there is a lack of the practical part due to the lack of a didactic module, Due to this arises the need to implement an automated module where you can perform practices on pneumatic and electro-pneumatic sequences, implementing an HMI and a PLC Logo for their respective automation, along with the creation of a manual of practices and a menu of the sequences that will be monitored by the HMI will improve the understanding of the theory and the practical application of these sequences in the real world. This module has several pneumatic, electrical, and electronic elements and parts such as acting cylinders, 3/2 valves, 5/2 valves, solenoid valves, push buttons, two positions selectors, 24 V power supply, PLC Logo, HMI screen, etc.